2007
DOI: 10.1007/s11274-007-9514-4
|View full text |Cite
|
Sign up to set email alerts
|

The effect of volatile fatty acids on the inactivation of Clostridium perfringens in anaerobic digestion

Abstract: The application of sludge digestion systems to remove pathogens has been employed to generate biosolids suitable for reuse in agriculture. Traditionally, temperature is considered the principal agent responsible for pathogen reduction in anaerobic digestion. However, other substances such as volatile fatty acids may also have an antimicrobial effect. The objective of this study was to assess the impact of fatty acid mixtures on the inactivation of C. perfringens over a range of digestion temperatures. An equim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 17 publications
1
27
0
Order By: Relevance
“…VFA concentration alone, or in combination with pH, temperature, exposure time and the degree of sensitivity of specific types of microorganisms is believed to impact upon injury of microorganisms in anaerobic digestion (Abdul & Lloyd ; Salsali et al . ). Although there have been numerous studies detailing the extent of pathogen removal achieved by different stabilization technologies (Aitken et al .…”
Section: Resultsmentioning
confidence: 97%
“…VFA concentration alone, or in combination with pH, temperature, exposure time and the degree of sensitivity of specific types of microorganisms is believed to impact upon injury of microorganisms in anaerobic digestion (Abdul & Lloyd ; Salsali et al . ). Although there have been numerous studies detailing the extent of pathogen removal achieved by different stabilization technologies (Aitken et al .…”
Section: Resultsmentioning
confidence: 97%
“…perfringens were induced to germinate during the thermal phase resulting in the inactivation of vegetative cells (Salsali et al . ). The same mechanism could have occurred with Cl.…”
Section: Discussionmentioning
confidence: 97%
“…It could be one reason for the highest methane yield obtained from sample 200 °C–0.5 h since sugars and short-chain organic fatty acids were relatively easier to be biodegraded by AD [42, 43]. It should be noted that sample 200 °C–2 h had higher amount of sugars and organic fatty acids (432 mg/g COD) compared to sample 170 °C–0.5 h (403 mg/g COD); however, it had significantly lower methane yield (259 mL CH 4 /g COD) compared to sample 170 °C–0.5 h (302 mL CH 4 /g COD), which indicated that other easily degradable organics might be present in 170 °C–0.5 h but not quantified in the present study.…”
Section: Discussionmentioning
confidence: 99%